Register Perawatan Wajah di Komunitas Media Sosial Facebook - Nashiroh, Tsalits Syafa’atun (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2023)
Every member of the community on Facebook can freely discuss something of mutual interest. However, the members usually use particular lexicons that can only be understood by the members and people with the same interest. This study aims to describe the forms of registers, semantic changes, and the function of registers used by the members of the Facebook community. Wardhaugh's perspective on registers is used in this study to restrict the concept of register. Meanwhile, Keraf and Biber's theory were applied to identify the meanings and the functions of the registers. This research applied descriptive qualitative method. The data of the registers used by Facebook community members in November 2022-Januari 2023 were collected by applying reading and note-taking techniques. Registers were analyzed based on the form, meaning, and function. The study found that the form of register used by skincare enthusiasts consisted of words, phrases, and abbreviations. The registers also changed in meaning in the type of narrowing, broadening, shifting, and metaphor. The use of registers predominantly meet the heuristic and representational functions. The forms and semantic changes in the use of registers can be caused by the situational characteristics of the community, such as users’ social characteristics, relation between users, communicative purposes, channel, and the topic. === Setiap anggota komunitas dalam Facebook dapat bebas berdiskusi mengenai sesuatu yang diminati bersama. Namun tidak jarang anggota menggunakan leksikon tertentu yang hanya dapat dipahami oleh anggota dan orang-orang dengan minat yang sama. Penelitian ini bertujuan untuk menguraikan bentuk-bentuk register, memaparkan perubahan-perubahan makna, dan fungsi penggunaan register oleh anggota komunitas Facebook. Perspektif Wardhaugh mengenai register digunakan penelitian untuk membatasi pengertian register. Sementara itu, teori Keraf dan Biber diaplikasikan untuk mengidentifikasi makna-makna dan fungsi register. Penelitian ini merupakan peneltian deskriptif kualitatif. Metode pengumpulan data yang digunakan yaitu menyimak dan mencatat register-register yang digunakan anggota komunitas Facebook pada bulan November 2922— Januari 2023. Register dianalisis berdasarkan bentuk, makna, dan fungsinya. Penelitian menemukan bahwa bentuk register penggemar perawatan wajah berupa kata, frasa, dan abreviasi. Register juga mengalami perubahan makna berupa penyempitan makna, perluasan makna, pergeseran makna, dan metafora. Penggunaan register lebih banyak memenuhi fungsi heuristik dan representasi. Bentuk dan perubahan yang terjadi pada penggunaan register tersebut dipengaruhi oleh karakteristik situasional, seperti karakteristik sosial pengguna, relasi antar pengguna, tujuan komunikatif, medium penyampaian, serta topik.